Investigating the ability of Saccharomyces cerevisiae and Lactobacillus plantarum on the reduction of aflatoxin B1, ochratoxin A, and zearalenone in dough and toast Bread - Alireza Haji Amiri; Leila Nateghi; Nazanin Zand (Iranian Journal of Microbiology)
Background and Objectives: Wheat and its derived products are high-risk commodities for aflatoxin contamination. The objective of this study was to investigate the effect of using Saccharomyces cerevisiae, Lactobacillus plantarum, and the dough fermentation and baking periods on reducing aflatoxin B1 (AFB1), ochratoxin A (OTA), and zearalenone (ZEA) toxins. Materials and Methods: Toast bread flour contaminated with AFB1, OTA and ZEA (10,10 and 400 ng/g) were separately treated with S. cerevisiae and L. plantarum (at a concentration of 108 CFU/g). The reduction of mycotoxins was examined immediately after dough preparation, at the end of fermentation, and after baking. Results: The type of microorganism, fermentation and baking significantly affected the reduction of mycotoxins (AFB1, OTA, and ZEA). After baking, neither AFB1 nor OTA were detected in any of the toast bread samples, with a 100% reduction observed in all treatments. In contrast, the percentage reduction of ZEA after baking compared with immediately after dough preparation ranged from 98.90% to 100%, and the percentage reduction of ZEA at the end of fermentation compared with immediately after dough preparation ranged from 97.80% to 99.57%. Conclusion: The findings of this study suggest that L. plantarum and S. cerevisiae can be used as additives or processing agents to decrease mycotoxins in fermented wheat foods.